Determinants of Individuals’ Understanding of Riba in Islamic Financial Transactions - Idel Waldelmi; Wita Dwika Listihana; Afvan Aquino; Novita Novita; Fatkhurahman Fatkhurahman (LPPM ISNJ Bengkalis, 2026)
Purpose - This study aims to analyze the determinant factors influencing the level of knowledge of Riba in sharia financial transactions. Specifically, the research examines the roles of religion, access to information, living necessities, culture, and financial alternatives in shaping public understanding of Riba. Method - The study employs a quantitative descriptive approach using primary data collected through structured questionnaires distributed to 132 respondents in Pekanbaru City who have previously engaged in sharia financial transactions. Data were analyzed using multiple linear regression to identify the significance and direction of influence of each independent variable on Riba knowledge. Findings - This study confirms that religion, access to information, living necessities, culture, and financial alternatives collectively influence Riba knowledge, the specific results clarify their distinct roles. Religion acts as the dominant moral foundation, access to information strengthens cognitive understanding, culture shapes social norms, living necessities create economic pressure, and financial alternatives provide limited explanatory influence. These findings imply that improving religious education and information accessibility is crucial for strengthening public understanding of sharia-compliant finance. Implications - The finding contributes theoretically by enriching the literature on Islamic financial literacy and empirically by providing evidence from an urban Muslim community. Practically, the findings offer insights for policymakers, Islamic financial institutions, and educators to design more effective literacy and outreach programs to reduce dependence on Riba-based transactions.